스트룹 간섭에 의한 시각작업기억의 왜곡 현상 - 김대규(Daegyu Kim); 현주석(Joo-seok Hyun) (인지과학, 2015)
The present study tested the effect of a top-down influence on recalling the colors of Stroop words. Participants remembered the colors of 1, 2, 3 or 6 Stroop words. After 1 second of a memory delay, they were asked to recall the color of a cued Stroop word by selecting out its corresponding color on a color-wheel stimulus. The correct recall was defined when the participants chose a color that was within ${±}45^{°}$ from the exact location of Stroop word's color on the color-wheel. Otherwise, the recall was defined as incorrect. The analyses of the frequency distribution of the participants' responses in the error trials showed that the probability of choosing the color-name of the target Stroop word was higher than the probability of other five color-names on the color-wheel. Further analyses showed that increasing the number of Stroop words to manipulate memory load did not affect the probability of the Stroop interference. These results indicate that the top-down interference by Stroop manipulation may induce systematic distortion of the stored representation in visual working memory. 장기기억 분야와 달리 시각작업기억에 대한 기억왜곡 연구사례는 흔치 않다. 본 연구는 시각작업기억 표상이 하향적 간섭에 의해 왜곡될 가능성을 관찰하고자 하였다. 기억표상의 질적 특성에 대한 직접적인 관찰을 위해서는 기억용량과 선명도를 추정하는 것이 중요하다. 본 연구에서는 색상환 과제를 통해 스트룹 단어의 색상에 대한 단기 회상을 요구하는 과정에서 발생하는 오류시행에 대한 분석을 통해 단어의 명칭에 의한 시각작업기억 표상의 왜곡 가능성을 조사하였다. 참가자들은 과제에서 500ms 동안 제시되는 1, 2, 3 혹은 6개의 스트룹 단어 항목의 색상을 기억하였다. 1초의 기억지연 시간 후, 기억이 요구된 스트룹 단어 중 단서가 지정하는 특정 단어의 색상을 회상해 색상환에서 선택 보고하였다. 색상환에서 회상이 요구된 자극의 실제 색상으로부터 ${±}45^{°}$ 이내의 색상을 선택했을 경우 정반응으로 간주 되었으며, 그 밖의 경우는 오반응으로 간주되었다. 오반응 시행에 대해 색상 선택의 분포 패턴을 분석한 결과, 보고 대상의 명칭 색상 범주에 기초한 회상 오류가 시행 전반에서 사용된 명칭 기반 평균 회상 오류를 상회하였다. 또한 항목개수 증가로 인한 기억부담의 증가는 이와 같은 스트룹 간섭에 의한 기억왜곡의 발생 확률에 큰 영향을 주지 않는 것으로 나타났다. 본 연구의 결과, 스트룹 자극에 대한 시각작업기억 표상에 대하여 자극의 명칭색상에 의한 체계적 왜곡 가능성이 관찰되었다. 이는 비교적 짧은 기간 활용되는 시각작업기억 수준의 표상 역시 장기기억과 마찬가지로 간섭에 의해 왜곡될 수 있음을 시사한다.